Interpersonal Movement Synchrony Responds to High- and Low-Level Conversational Constraints - Paxton, Alexandra; Dale, Rick (Frontiers in Psychology, 2017)
Much work on communication and joint action conceptualizes interaction as a dynamical system. Under this view, dynamic properties of interaction should be shaped by the context in which the interaction is taking place. Here we explore interpersonal movement coordination or synchrony—the degree to which individuals move in similar ways over time—as one such context-sensitive property. Studies of coordination have typically investigated how these dynamics are influenced by either high-level constraints (i.e., slow-changing factors) or low-level constraints (i.e., fast-changing factors like movement). Focusing on nonverbal communication behaviors during naturalistic conversation, we analyzed how interacting participants' head movement dynamics were shaped simultaneously by high-level constraints (i.e., conversation type; friendly conversations or arguments) and low-level constraints (i.e., perceptual stimuli; non-informative visual stimuli vs. informative visual stimuli). We found that high- and low-level constraints interacted non-additively to affect interpersonal movement dynamics, highlighting the context sensitivity of interaction and supporting the view of joint action as a complex adaptive system.